Impaired muscarinic modulation of the rat prelimbic cortex in neuropathic pain is sexually dimorphic and associated with cold allodynia - Jefferson, Taylor; Kim, Haram R.; Martina, Marco (Frontiers in Cellular Neuroscience, 2023)
Cholinergic modulation of the brain cortex is critical for cognitive processes and altered cholinergic modulation of the prefrontal cortex is emerging as an important mechanism of neuropathic pain. Sex differences in pain prevalence and perception are well known, yet the precise nature of the mechanisms responsible for sexual dimorphism in chronic neuropathic pain are poorly understood. Here we investigated potential sex differences in cholinergic modulation of layer 5 commissural pyramidal neurons of the rat prelimbic cortex in control conditions and in the SNI model of neuropathic pain. We discovered quantitative differences between cholinergic modulation in cells from male and female rats, and that these differences are amplified in the neuropathic pain condition. Interestingly, in neuropathic pain rats, cholinergic excitation of pyramidal neurons was more severely impaired in males than in females. Finally, we found that selective pharmacological blockade of the muscarinic M1 subunit in the prefrontal cortex is sufficient to induce cold (but mot mechanical) allodynia in naïve animals of both sexes.